2003
DOI: 10.1152/japplphysiol.01105.2002
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic rhinometry in dog and cat compared with a fluid-displacement method and magnetic resonance imaging

Abstract: . Acoustic rhinometry in dog and cat compared with a fluid-displacement method and magnetic resonance imaging. J Appl Physiol 95: 635-642, 2003. First published April 18, 2003 10.1152/japplphysiol.01105. 2002.-An increasing number of studies have used acoustic rhinometry (AR) for study of pharmacological interventions on nasal cavity dimensions in dogs and cats, but there have been no attempts to validate AR in these species. This is done in the present study. We compared area-distance relationships of nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Another noninvasive technique is magnetic resonance imaging (MRI) assessment, which has advantages similar to micro-CT of being repeatable and nonterminal. However, a study of MRI in comparison with the fluid displacement method in dogs and cats indicated that cross-sectional area of the sinus lumen was limited by the fact that its definition was dependent on subjective choices made by the image assessor, making MRI unsuitable as a gold standard of sinus measurement (45). Although we had obtained some interesting and congruent data with the 2-D linear cumulative-width measures of micro-CT images (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Another noninvasive technique is magnetic resonance imaging (MRI) assessment, which has advantages similar to micro-CT of being repeatable and nonterminal. However, a study of MRI in comparison with the fluid displacement method in dogs and cats indicated that cross-sectional area of the sinus lumen was limited by the fact that its definition was dependent on subjective choices made by the image assessor, making MRI unsuitable as a gold standard of sinus measurement (45). Although we had obtained some interesting and congruent data with the 2-D linear cumulative-width measures of micro-CT images (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…9 and 10, this would be particularly true for the distal sinus regions. Indeed, a series of studies comparing acoustic rhinometry with the fluid displacement method in dogs, cats, guinea pigs, and rats indicated that acoustic rhinometry underestimated sinus vol-ume by an average of approximately 15-30% across those species (44,45). Although noninvasive, for the reasons above, we judged the acoustic rhinometry method to be unacceptable as a gold standard for our purposes, against which to compare results from our noninvasive micro-CT methods.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic rhinometry has been used in experimental guinea pigs [6], dogs, cats [7], and rats [8]. However, little information on its application in non-human primates (NHPs) has been accumulated to date.…”
Section: Introductionmentioning
confidence: 99%